2015
DOI: 10.1371/journal.pone.0123013
|View full text |Cite
|
Sign up to set email alerts
|

Faecalibacterium prausnitzii Strain HTF-F and Its Extracellular Polymeric Matrix Attenuate Clinical Parameters in DSS-Induced Colitis

Abstract: A decrease in the abundance and biodiversity of intestinal bacteria within the Firmicutes phylum has been associated with inflammatory bowel disease (IBD). In particular, the anti-inflammatory bacterium Faecalibacterium prausnitzii, member of the Firmicutes phylum and one of the most abundant species in healthy human colon, is underrepresented in the microbiota of IBD patients. The aim of this study was to investigate the immunomodulatory properties of F. prausnitzii strain A2-165, the biofilm forming strain H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 27 publications
1
107
0
Order By: Relevance
“…Similar elements have been reported in the cell envelope of Gemmiger formicilis (Gossling & Moore, 1975;Salanitro et al, 1976), a member of the family Ruminococcaceae moderately related to strains 585-1 T and 668 based on 16S rRNA gene sequencing. Other related members of the family, A. agile and F. prausnitzii, were shown, however, to have a typical Gram-positive cell-wall architecture with thin murein layer, despite their variable Gram staining (Zellner et al, 1996;Rossi et al, 2015). In addition, a thin microcapsule was visible on the surface of strain 585-1 T .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Similar elements have been reported in the cell envelope of Gemmiger formicilis (Gossling & Moore, 1975;Salanitro et al, 1976), a member of the family Ruminococcaceae moderately related to strains 585-1 T and 668 based on 16S rRNA gene sequencing. Other related members of the family, A. agile and F. prausnitzii, were shown, however, to have a typical Gram-positive cell-wall architecture with thin murein layer, despite their variable Gram staining (Zellner et al, 1996;Rossi et al, 2015). In addition, a thin microcapsule was visible on the surface of strain 585-1 T .…”
mentioning
confidence: 98%
“…Depletion of this organism from the faecal microbiota has been implicated in the pathogenesis of inflammatory bowel disease (IBD; Sokol et al, 2009). Moreover, recent studies have confirmed antiinflammatory activity of F. prausnitzii live cultures, cell supernatants and certain purified components in animal models of IBD (Qu evrain et al, 2015;Rossi et al, 2015). Interestingly, despite its extreme air-sensitivity, F. prausnitzii may actually benefit from low oxygen concentrations by using it for NADH regeneration through an extracellular electron shuttle (Khan et al, 2012).…”
mentioning
confidence: 99%
“…Similarly, protection against C. rodentium infection by Bifidobacterium breve UCC2003 was dependent on the presence of its exopolysaccharide (21). Furthermore, it was described that an extracellular polymeric matrix, isolated from Faecalibacterium prausnitzii, displayed anti-inflammatory activity in the mouse dextran sodium sulfate colitis model (22).…”
mentioning
confidence: 99%
“…In addition, alterations and interventions in the gut ecosystem may cause diseases, as was discovered in the Nobel Prize winning case of Helicobacter pylori, which can cause ulcerative colitis (Marshall andWarren, 1984, Ahmed, 2005). The influence of bacteria on host health can differ between strains, as was shown for the influence of F. prausnitizii in mice (Rossi, et al, 2015, Song, et al, 2016) and the well-described differences between probiotic strains in human (Hill, et al, 2014). So, to study the causal relationships between bacterial species and compositions in general, we need to culture not only all species, but preferably multiple strains per species.…”
Section: The Role Of the Faecal Microbiota In Health And Diseasementioning
confidence: 93%
“…These cases included studies using specific probiotic strains (Derrien and van Hylckama Vlieg, 2015), including bifidobacteria (Tojo, et al, 2014) and lactobacilli (Wang, et al, 2015). The use of other potential beneficial bacteria in intervention studies is limited to mouse models and include members of the natural microbiota and possible therapeutic microbes, such as Eubacterium hallii , Faecalibacterium prausnitzii (Rossi, et al, 2015),…”
Section: Causality and Using Genome-scale Metabolic Models In Gut Micmentioning
confidence: 99%